DIMENSI KUALITAS AUDIT PENENTU KEPUASAN AUDITEE (STUDI PADA PEMERINTAH KABUPATEN MALUKU BARAT DAYA) - Leiwakabessy, Theophilia Fina F (Jurnal Akuntansi, 2021)
Perceptions of quality audits vary widely depending on the viewpoint of the judge. In general, audit quality is always reviewed by the auditor. The quality of audit implementation always refers to established standards including general standards, work standards, and reporting standards, while the users of audit services are often forgotten. Good audit quality will have an impact on audit service users (auditee).This study was aimed to exemined the effect of audit quality dimensions including auditor’s reputation, expertise, capability, independence, responsiveness and emphaty to client satisfaction. The population of this study are goverment officer in Maluku Barat Daya. Sampling was conducted using a judgement sampling method and number of samples are 44 respondents. Technique of data collection is survey by using questionnaires. Analysis using multiple regression analysis. The results showed that auditor reputation, capability, and emphaty have a positive and significant effect on auditee satisfaction, while the auditor expertise, independence, responsiveness do not significantlyaffect the auditee satisfaction.